A Solvent‐Free Hot‐Pressing Method for Preparing Metal–Organic‐Framework Coatings. (5th February 2016) - Chen, Yifa; Li, Siqing; Pei, Xiaokun; Zhou, Junwen; Feng, Xiao; Zhang, Shenghan; Cheng, Yuanyuan; Li, Haiwei; Han, Ruodan; Wang, Bo
Abstract: Metal–organic frameworks (MOFs), with their well‐defined pores and rich structural diversity and functionality, have drawn a great deal of attention from across the scientific community. However, industrial applications are hampered by their intrinsic fragility and poor processability. Stable and resilient MOF devices with tunable flexibility are highly desirable. Herein, we present a solvent‐ and binder‐free approach for producing stable MOF coatings by a unique hot‐pressing (HoP) method, in which temperature and pressure are applied simultaneously to facilitate the rapid growth of MOF nanocrystals onto desired substrates. This strategy was proven to be applicable to carboxylate‐based, imidazolate‐based, and mixed‐metal MOFs. We further successfully obtained superhydrophobic and "Janus" MOF films through layer‐by‐layer pressing. This HoP method can be scaled up in the form of roll‐to‐roll production and may push MOFs into unexplored industrial applications.